A randomized controlled trial for evaluation of lower abdominal laparoscopic cholecystectomy. Issue 2 (4th March 2018) - Xu, Li; Tan, Haidong; Liu, Liguo; Si, Shuang; Sun, Yongliang; Huang, Jia; Atyah, Manar; Yang, Zhiying
Abstract: Background: To improve minimally invasive outcomes, we designed a new procedure, lower abdominal laparoscopic cholecystectomy (LALC). This study was conducted to evaluate the effects of LALC versus classical (CLC) and single-incision (SILC) laparoscopic cholecystectomy on reducing systemic acute inflammatory response, improving cosmesis, and postoperative pain relief. Material and methods: Beginning from July 2014, 105 patients meeting the inclusion criteria were randomly assigned to three groups: LALC, CLC, and SILC. The primary endpoint was the determination of systemic inflammatory response to the surgery. Other outcome measures included cosmesis, postoperative pain, and perioperative indices. Results: Each of the three groups consisted of 35 patients. The duration of the operation was significantly longer in the SILC group ( p = .005). The rates of adverse events were similar. Changes in interleukin-6 ( p  =  .001) and tumor-necrosis factor-α ( p  =  .016) measured before and after surgery differed significantly; patients who underwent LALC had the smallest change in inflammatory response. Cosmesis scores at one ( p  =  .002) and 12 ( p  =  .004) weeks after surgery favored LALC and SILC. Significant differences in pain scores at four ( p  =  .011) and 12 h ( p  =  .024) postoperatively were also observed. Conclusions: In selected patients, LALC shows more advantages in terms of lower systemic inflammatory response, improved cosmesis, and a favorable postoperative pain profile when compared with CLC and SILC.